(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease mostly affecting women of child baring age. It is a multifactorial disease and may affect multiple organs of the body including central nervous system, hematological and immunological system. Various studies have reported variable incidence of cognitive impairment in SLE. The aim of the present study was to assess the frequency and factors affecting cognitive impairment in patients with SLE. Subjects and Methods: This cross-sectional study was conducted at Department of Rheumatology & Immunology, Sheikh Zayed Hospital, Lahore from January to July 2018. Diagnosed cases of SLE, on basis of American College of Rheumatology Revised Classification Criteria of SLE, visiting outpatient department and Rheumatology ward of the hospital were included in the study. Patients having any organic brain disease or those with known psychiatric illness were excluded from the study. Mini-mental state examination (MMSE) and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) were calculated for the patients. Results: Attention and recall, language and memory were identified as commonly affected domains of cognitive impairment in SLE patients. Positive correlation between duration of the disease and steroid dose was found. Disease activity score was negatively correlated with age, duration of the disease and steroid dose. Conclusion: Cognitive impairment is present in SLE patients. Age, duration of disease and steroid dose has no significant effect on cognitive impairment in SLE patients.